2021
DOI: 10.1371/journal.pone.0246435
|View full text |Cite
|
Sign up to set email alerts
|

Validation of a novel multiplex real-time PCR assay for Trypanosoma cruzi detection and quantification in açai pulp

Abstract: In Brazil, orally acquired T. cruzi infection has become the most relevant transmission mechanisms from public health perspective. Around 70% of new Chagas disease cases have been associated with consumption of contaminated food or beverages. Açai (Euterpe oleracea and Euterpe precatoria) is currently one of the most commercialized Amazonian fruits in the Brazilian and international markets. Therefore, it has become important to incorporate in the production process some procedures to measure out effective hyg… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 45 publications
0
10
0
Order By: Relevance
“…These berries have become popular globally and are currently the most commercialised Amazonian fruit in the Brazilian and international markets. A study of the presence of DNA from T. cruzi showed that it could be detected in a 20% of acai samples [13]. Hence it is essential to implement hygienic measures and food quality controls in the commercial chain.…”
Section: Resultsmentioning
confidence: 99%
“…These berries have become popular globally and are currently the most commercialised Amazonian fruit in the Brazilian and international markets. A study of the presence of DNA from T. cruzi showed that it could be detected in a 20% of acai samples [13]. Hence it is essential to implement hygienic measures and food quality controls in the commercial chain.…”
Section: Resultsmentioning
confidence: 99%
“…Poverty-related Chagas disease, which is, e.g., endemic in resource-limited tropical settings in South America [1], has been of increasing interest for the development of molecular diagnostic test assays in the recent two decades [2][3][4][5][6][7][8][9][10][11][12][13][14][15]. However, different from other systemic parasitic diseases such as malaria, for which excellent diagnostic accuracy of molecular diagnostic approaches has been repeatedly shown [16][17][18], the reliability of molecular techniques for the diagnosis of Chagas disease has often been less convincing in previous studies [8,[10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Oral transmitted T. cruzi infection through consumption of açaí juice has been detected in several locations of Brazil but has not been reported in Bolivia yet. There are reports of oral transmitted infections in the Brazilian municipalities of Coari (Finamore-Araujo et al 2021), Manaos (Santana et al 2019), Amazonas State, Pará State (de Mattos et al 2017) and Amapá State (Rodrigues 2015). However, most of these municipalities are still far from the Bolivian border, with few reports (less than 10 cases) in the neighbor states of Acre and Rondonia (Shikanai-Yasuda and Carvalho 2012).…”
Section: Introductionmentioning
confidence: 99%